2019
DOI: 10.1002/chem.201903087
|View full text |Cite
|
Sign up to set email alerts
|

Electron Density Studies in Materials Research

Abstract: Rational material design requires a deep understanding about the relationship between the structure and properties of materials, which are both intimately related to their chemical bonding. Through the experimentally observable electron density, chemical bonding can be understood from experimental and theoretical points of view on an equal footing, and advances in accurate X‐ray diffraction measurements and computational techniques over the past decades have provided access to electron density distributions in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 192 publications
(208 reference statements)
1
22
0
Order By: Relevance
“…The important development in the topological analysis, specifically, the atoms in molecules (AIM) theory which developed by Bader and his group, is to study both experimental and theoretical electron density distributions. Additionally, this approach provides a useful tool for studying various interactions in a molecular system (12)(13)(14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…The important development in the topological analysis, specifically, the atoms in molecules (AIM) theory which developed by Bader and his group, is to study both experimental and theoretical electron density distributions. Additionally, this approach provides a useful tool for studying various interactions in a molecular system (12)(13)(14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…So far,n oX -ray electrond ensity (ED) analysish as been attempted to providee xperimental evidencef or the electronic structure. [8][9][10] As the ED imparts the physical properties of a system, it is clearlyi mportant to provide an understanding of the specific chemicalb onding and atomic valences tates in FeSb 2 .H owever,t he study of FeSb 2 by X-ray ED analysis is a great challenge becausethe structure contains heavya toms,i n whicht he valence electrons only contribute weakly to the diffractedi ntensities. An X-ray ED study of the similarly challenging thermoelectric material CoSb 3 has been reported [11,12] with as uitability factor, S ¼ V= P i;unit cell n 2 core;i , [13] of 0.01, which is much lower than the values of 5-10 typically seen for organic compounds.…”
Section: Introductionmentioning
confidence: 99%
“…The origin of the extraordinary temperature dependence of the transport properties has been heavily debated, and theoretical and experimental data suggest that they are linked to a combination of phonon‐drag, electron‐correlation effects, and anti‐site defects to generate impurity in‐gap electronic states. So far, no X‐ray electron density (ED) analysis has been attempted to provide experimental evidence for the electronic structure . As the ED imparts the physical properties of a system, it is clearly important to provide an understanding of the specific chemical bonding and atomic valence states in FeSb 2 .…”
Section: Introductionmentioning
confidence: 99%
“…[1,2] Due to the progress in quantum chemistry calculations, the method has gained popularity and finds numerous applications in studies of organic and inorganic compounds. [3][4][5][6][7][8][9][10][11][12][13][14][15] In particular, the method helps to identify changes in chemical bonds and mechanisms of phase transitions under high pressure. [16][17][18][19][20][21][22][23][24][25][26] At the same time, the use of topological analysis for the understanding of bonding in layered compounds is not numerous.…”
Section: Introductionmentioning
confidence: 99%